Evaluation of interleukin-6, leukotriene b-4, and nitric oxide levels in exhaled breath condensate of asymptomatic obese individuals: Are obese patients under risk of developing asthma? - Gegin, Savaş; Çelikel, Serhat; Çelik, Deniz; Pazarlı, Ahmet Cemal (AVES, 2020)
Objective: If systemic inflammation in relation with obesity causes asthma, the detection of increased airwayinflammation among obese individuals who do not have any respiratory symptoms can be also beneficial inindentifying obese patients who are at risk of developing asthma. The aim of this study was to evaluate thesystemic and airway inflammation of asymptomatic obese and non-obese individuals.Materials and Methods: Obese and non-obese individuals with no respiratory symptoms were included.Inflammatory biomarkers such as C-reactive protein (CRP), exhaled breath condensate (EBC) interleukin-6(IL-6), EBC leukotriene B-4 (LTB-4), and EBC nitric oxide (NO) levels of obese and non-obese individualswere determined.Results: Forty-five obese individuals (body mass index [BMI]?30) and 31 non-obese individuals (BMI?25)as a control group were included in this study. The mean age of the obese group (38.7±11.4 years) wassignificantly higher than the one of the non-obese group (29.5±8.6 years; p<0.001). There was no significant relationship between gender and BMI (?²=1.471, p=0.225). CRP levels were significantly higher in theobese group (6.94±8.28) than the non-obese group (3.29±0.39; p<0.001). The levels of EBC IL-6 in obeseand non-obese group were found as 22.61±12.53 and 21.08±14.39, respectively (p=0.624). There was nosignificant difference between EBC NO levels of the obese group and non-obese group (24.35±10.9 vs.21.56±7.83; p=0.226). No significant difference was found between the EBC LTB-4 level in the obese groupand the non-obese group (36.39±89.82 vs. 16.64±17.45; p=0.231).Conclusion: Increased systemic inflammation in obese individuals who had no respiratory symptoms mightindicate the tendency of asthma. However, airway inflammation was not significantly different betweengroups. Therefore the relationship between obesity and asthma should be investigated in future large-scalestudies determining the direct effects of adipokines on airways.
Keywords: Obesity; Airway Inflammation; Systemic Inflammation